Community Acquired Pseudomonas aeruginosa Pneumonia in a Young Athlete Man: A Case Report and Literature Review - Rahdar, Hossein A.; Kazemian, Hossein; Bimanand, Lida; Shahraki-Zahedani, Shahram; Feyisa, Seifu Gizaw; Taki, Elahe; Havaei, Seyed Asghar; Karami-Zarandi, Morteza (Infectious Disorders - Drug Targets, 2018)
Pseudomonas aeruginosaisa commonly known as nosocomial infection agent but rarely previously healthy people are infected by P. aeruginosa. Here we report Community Acquired Pneumonia (CAP) in a 27 year old male athlete. 15 published P. aeruginosa CAP case reports were reviewed. 53.3% of patients were female and 46.67% were male. The mean age was 44 years old (SD: ±13.54). In 8 reports it is mentioned that the patient was a smoker. Fatality rate was 46.6% and death rate was not significantly different between selected antibiotic regimen, sex and smoking in patient's outcome. Chest strike can be a risk factor for P. aeruginosa CAP in athlete people. Our reported patient treated by ciprofloxacin 500 mg per day and healed without any Secondary complication. Fast, timely diagnosis and treatment is critical in Community Acquired P. aeruginosa pneumonia outcome.
Keywords: Pathogen